Handedness preference and switching of peptide helices. Part II: Helices based on noncoded α‐amino acids‡. (30th January 2015) - Crisma, Marco; De Zotti, Marta; Formaggio, Fernando; Peggion, Cristina; Moretto, Alessandro; Toniolo, Claudio
<x xml:space="preserve">Abstract</x> In this second part of our review article on the preferred screw sense and interconversion of peptide helices, we discuss the most significant computational and experimental data published on helices formed by the most extensively investigated categories of noncoded α‐amino acids. They are as follows: (i) N‐alkylated Gly residues (peptoids), (ii) Cα‐alkylated α‐amino acids, (iii) Cα, β‐sp2 configurated α‐amino acids, and (iv) combinations of residues of types (ii) and (iii). With confidence, the large body of interesting papers examined and classified in this editorial effort will stimulate the development of helical peptides in many diverse areas of biosciences and nanosciences. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.